IPR 106: new Arabica coffee cultivar, resistant to some Meloidogyne paranaensis and M. incognita nematode populations of Paraná - Sera,Gustavo Hiroshi (2020)
Abstract Cultivar IPR 106 resulted from a spontaneous hybridization between “Icatu IAC 925” and an unknow dwarf plant. It is a dwarf cultivar with high rusticity, late ripening cycle, large grains, excellent cup quality and resistance to some populations of the nematodes Meloidogyne paranaensis and M. incognita found in the state of Paraná.